PENGARUH PERSEPSI TENTANG BRAND IMAGE DAN STATUS EKONOMI KELUARGA TERHADAP KEPUTUSAN MAHASISWA KULIAH STRATA 1 DI PENDIDIKAN EKONOMI UNIVERSITAS RIAU - Wisma Nengsih; Sumarno '; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this study was to find out : influence of brand image and family financial ability on student’s decision to enroll into economic education major in riau university do simultaneously and partial. The population is all college students years entry 2014 and 2015 Saber totaling 195 college students with a sample of 66 college students. Based on the results of data analysis simultaneously is concluded that in mind the significant value on the table coeffisients 0,000 less than the critical value of 0.05. Then obtained this result shows that the brand image and family financialability significantly affects student’s decision in to enroll into economic education major in riau university the years entry 2014 and 2015. Based on the regression coefficient if Brand Image increased by 1%, the student’s decision will also increase by 0339 or 33.9%, and if family fiancial ability increased by 1%, the student’s decision will also increase by 0.12 or 12%, Coefficient is positive, it means there is a positive relationship between the brand image and family financial ability with student’s decision, the rise brand image and famility financial ability then the ride anyway student’s decision. Judging from R Square of 0.,481 this shows that the independent variables used in this study could affect the dependent variable by 48, 1%.Key Word : student’s decision,brand image, family financial ability.